Association between Breast Feeding And Breast Cancer: A Case Control Study in Erbil - Sherwan Aziz1, Abdulqadir Zangana2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background and Objective: Breast cancer is the most common cancer that threatens life of women all over theworld. In Iraq it is the most common cancer; 5141 new cases of breast cancer registered in 2018 comprising36.7% of all women cancers and 20.3% of all cancers in both sexes. Breast cancer is a multifactorial diseasemany of the risk factors are modifiable, one of these factors is breastfeeding.The aim of the study is investigating the association of duration of breastfeeding with breast cancerdevelopment, and comparing the risk in premenopausal and postmenopausal women.Patients and methods: This study is a prospective case control study conducted in Erbil Breast Clinic andErbil teaching hospital in Erbil city from January 31, 2016 to June 31, 2016.140 women with histopathologically proved breast cancer compared with 160 women with no breast cancerin regard to total duration of breastfeeding.Results: Among the 140 women with breast cancer; 66.4% women were pre-menopausal, and 33.6% womenwere postmenopausal, among the 160 women in the control group; 73.1% women were pre-menopausal,and 26.9% were postmenopausal.Among postmenopausal women; 19.15% of women with breast cancer never practiced breastfeeding, whileonly 2.33% of women in the control group never practiced breastfeeding which was statistically different.Conclusion: Postmenopausal women who did not practice breastfeeding and parous women who breastfedtheir children less than 12 months are at increased risk of breast cancer.